2018
DOI: 10.23881/idupbo.018.1-3i
|View full text |Cite
|
Sign up to set email alerts
|

Evaluación De La Precipitación Distribuida en La Cuenca Katari Basado en Tecnología Satelital Y Productos Derivados

Abstract: RESUMENLa medición de la precipitación espacial, en alta resolución, es una variable crucial en la modelación hidrológica de cuencas, pero debido a las limitantes con respecto a la cantidad y distribución de pluviómetros, se hace necesario la generación de datos utilizando productos satelitales de precipitación. Para este estudio se usaron los productos: GSMaP, CHIRPS y GMET, cada uno con una resolución espacial y temporal diferente. El área de estudio es la cuenca Katari, al noreste de la ciudad del Alto y pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Similarly, [48] reported that the accuracy of CHIRPS estimates was dependent on geographic and climatic characteristics across contrasting topographies of South America. The study conducted in the Highland area of Bolivia (Katari basin) using CHIRPS satellite data [49] concludes that CHIRPS data tend to overestimate rainfall. The ME results for Laykacota station in both CHIRPS and IMERG assessments showed overestimation of rainfall by the SREs, likely due to its geographical proximity to the Katari basin.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, [48] reported that the accuracy of CHIRPS estimates was dependent on geographic and climatic characteristics across contrasting topographies of South America. The study conducted in the Highland area of Bolivia (Katari basin) using CHIRPS satellite data [49] concludes that CHIRPS data tend to overestimate rainfall. The ME results for Laykacota station in both CHIRPS and IMERG assessments showed overestimation of rainfall by the SREs, likely due to its geographical proximity to the Katari basin.…”
Section: Discussionmentioning
confidence: 99%
“…The KRB is located in the Andes region near La Paz, which is the capital of Bolivia in South America. This river basin covers 2955 km 2 , and its altitude ranges from 3800 to 5720 meters above sea level, with slopes from 4% to 90% [53]. The mean temperatures in the last 15 years have oscillated between −5 • C and 15 • C, and the average precipitation ranges from 470 to 742 mm [54].…”
Section: Transdisciplinary Learning Communities As Action Research Mementioning
confidence: 99%